Structure-property Relationships Reported for the New Drugs Approved in 2022 - Choi, Kihang (Mini Reviews in Medicinal Chemistry, 2024)
Background: The structure–property relationship illustrates how modifying the chemical structure of a pharmaceutical compound influences its absorption, distribution, metabolism, excretion, and other related properties. Understanding structure–property relationships of clinically approved drugs could provide useful information for drug design and optimization strategies.Method: Among new drugs approved around the world in 2022, including 37 in the US, structure– property relationships of seven drugs were compiled from medicinal chemistry literature, in which detailed pharmacokinetic and/or physicochemical properties were disclosed not only for the final drug but also for its key analogues generated during drug development.Results: The discovery campaigns for these seven drugs demonstrate extensive design and optimization efforts to identify suitable candidates for clinical development. Several strategies have been successfully employed, such as attaching a solubilizing group, bioisosteric replacement, and deuterium incorporation, resulting in new compounds with enhanced physicochemical and pharmacokinetic properties.Conclusion: The structure-property relationships hereby summarized illustrate how proper structural modifications could successfully improve the overall drug-like properties. The structure–property relationships of clinically approved drugs are expected to continue to provide valuable references and guides for the development of future drugs.
Keywords: candidate selection